Junior High School Students' Conceptual Understanding of Flat-Sided Geometric Shapes through APOS Theory: A Qualitative Study - Muh. Khaedir Lutfi; Endang Cahya Mulyaning A; Fitri Anisa Kusumastuti (Universitas Sarjanawiyata Tamansiswa, 2026)
Research on students' difficulties in geometry has mostly emphasized errors and formula mastery, while fewer studies have examined how junior high school students construct three-dimensional geometric concepts through APOS theory. This qualitative descriptive study analyzes eighth-grade students' conceptual understanding of cubes and prisms in flat-sided geometric shapes using the APOS framework. Participants were 28 eighth-grade students in Tangerang Regency who had studied cubes and prisms. Data were collected through five open-ended diagnostic questions mapped to Action, Process, Object, and Schema indicators and through semi-structured interviews. The results showed that 10 students (35.7%) were at the Action stage, 9 students (32.1%) at the Process stage, 6 students (21.4%) at the Object stage, and 3 students (10.8%) at the Schema stage. Most students could apply formulas but had difficulty explaining why formulas worked, coordinating two- and three-dimensional representations, and integrating base area, height, volume, and context. The novelty of this study lies in using APOS as a diagnostic framework for identifying were students' cognitive construction stalls in junior high school three-dimensional geometry. The findings suggest that geometry instruction should include visualization, manipulation, and reflective explanation to support transitions between APOS stages.